Use of polymethylpentene films as release films in composite molding processes.
Patent Information
- Application Number
- JP2023564102
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-23
- Filing Date
- 2022-04-21
- Publication Date
- 2025-04-01
AI Technical Summary
Existing methods for manufacturing fiber-reinforced polymer composites face challenges such as time-consuming processes, high part-to-part variations, and imperfections like wrinkles and contamination, which are not adequately addressed by current forming techniques that do not consider the rheological behavior and curing properties of the composite material.
A dual diaphragm mechanical thermoforming process using a single-layer polymethylpentene (PMP) film as a release film, allowing for the formation of complex three-dimensional composite structures by considering the rheological behavior and curing properties, with the film capable of withstanding high temperatures and providing self-peelability to prevent surface defects and contamination.
The process enables rapid, reliable, and large-scale manufacturing of composite parts with superior surface finish and thermal/mechanical performance, suitable for automotive and aerospace applications, without film breakage or surface imperfections, and allows for easy recycling of the film.
Abstract
Description
[Technical field]
[0001] Fiber-reinforced polymer composites are widely used in many industries, including aerospace, automotive, marine, industrial, construction, and a variety of consumer products, and are often chosen because they exhibit high strength and corrosion resistance, especially in harsh environments, while being lightweight. Fiber-reinforced polymer composites are typically manufactured from either pre-impregnated materials or resin infusion processes.
[0002] Pre-impregnated materials, or "prepregs", generally refer to fibers (such as carbon fibers) that have been impregnated with a curable matrix resin (such as epoxy). The resin content in prepregs is relatively high, typically 40% to 65% by volume. Multiple plies of prepregs can be cut to size for stacking, and then subsequently assembled and molded in a molding tool. If the prepregs cannot be easily conformed to the shape of the molding tool, heat may be applied to the prepregs to gradually deform them to the shape of the molding surface. Fiber-reinforced polymer composites can also be produced by liquid molding processes, including resin infusion techniques. In a typical resin infusion process, dry fibers bound with a binder are placed into a mold as a preform, and then liquid matrix resin is directly injected (or infused) in situ. After injection (or infusion), the resin-infused preform is cured to obtain the finished composite article.
[0003] For both types of materials, the process of three-dimensional shaping (or molding) of the composite material is critical to the appearance, properties, and performance of the final molded product. Preforms are still typically formed into precise shapes using hand layup processes, which are time-consuming and often result in high part-to-part variability. Although other, less manual methods exist for shaping composite materials (such as vacuum forming, which may use pins, robots, and / or actuators to aid in part formation), such methods have their own drawbacks and shortcomings. In addition, such methods are often time-consuming and do not take into account the rheological behavior and curing characteristics of the composite material. Furthermore, products of such processes are still prone to wrinkles and other defects.
[0004] Considering the potential drawbacks of composite processing, including processing time, part-to-part variability, and product contamination, there remains a need to develop faster, improved, and more reliable assemblies and methods. It is also desirable to provide methods that take into account rheological behavior and curing characteristics, and where possible, maximize the use of existing equipment (e.g., metal stamps or presses).
[0005] A method for forming composite materials implementing a double diaphragm mechanical thermoforming process has been successfully developed with the goal of providing an assembly for isolating the composite material from environmental contaminants and a forming process that not only addresses the shortcomings and deficiencies of other methods known in the art, but also takes into account the rheological behavior and curing characteristics of the composite material, and also allows the possibility of using existing infrastructure and equipment. This method provides an effective and efficient means for producing complex three-dimensional composite structures in an automated manner. Thus, three-dimensional composite structures can be produced quickly, repeatedly, and on a large scale.
[0006] For example, this dual diaphragm molding technology has evolved rapidly and is now available for use in full scale automotive manufacturing.
[0007] The amount of composites in the automotive range market continues to grow due to the ever-increasing need for lightweighting of various parts. Similarly, the amount of composites in the aerospace and urban air mobility (UAM) markets is predicted to increase significantly over the next decade. To meet this growing demand, the manufacturing speed of parts needs to increase. Therefore, original equipment manufacturers (OEMs) are increasingly turning to speed-capable manufacturing techniques such as compression molding to meet future speed targets.
[0008] However, the automotive, UAM, and aerospace markets do not necessarily have the same technical specifics and specific speed and performance requirements. In particular, the aerospace and UAM markets require high curing temperatures T cure There is a demand for higher temperature cure / high performance resin chemistries, typically between about 150 and about 190°C.
[0009] The method using the double diaphragm mechanical process comprises a diaphragm. In this context, the term "diaphragm" refers to any barrier that divides or separates two different physical regions. The term "diaphragm structure" is also used to refer to an assembly of one or more diaphragms that define an exterior space and an isolated interior space (e.g., an area within an enclosed pocket and an area outside the enclosed pocket). In general, the material used to manufacture the diaphragm is not particularly limited and may be, for example, rubber, silicone, plastic, thermoplastic, or similar material, or may include a film selected from a plastic layer or an elastic layer. The diaphragm may be composed of a single material or may include multiple materials, for example arranged in layers.
[0010] Films exist that are used as diaphragms, which contain one or more layers. However, these films can have significant limitations and poor performance that may prevent their use, especially in the aerospace and UAM markets. In particular, their melting temperatures are too low for use in these markets, limiting the achievable cure temperature range (<150°C), and they have limited thermal and mechanical capabilities. In particular, this is due to the fact that films are generally not suitable for use in the aerospace and UAM markets, as they are generally not suitable for use in the aerospace and UAM markets. cure This can cause the film to melt and / or break when forming the composite part.
[0011] Furthermore, multilayer films are difficult to use. In particular, certain existing films with unbalanced multilayer composition also cause film curl during assembly, limiting the robustness and ease of use of the process. In addition, the use of multilayer films limits the recycling possibilities of these films, or at least requires the construction of more complicated and expensive processes.
[0012] Therefore, a need remains for a film that exhibits an extended temperature range for use in high temperature dual diaphragm mechanical processes for forming complex structural composite parts that exhibits a visually good surface finish and significantly reduces the process tact time without compromising the thermal and mechanical performance of the final part.
[0013] In addition to these requirements, one of the desired properties of these films is the ability to self-release. However, at high temperatures the films can have the drawback of sticking to the composite parts, which can result in a poor surface finish, among other things.
[0014] To address these shortcomings, the present disclosure provides for the use of certain films (individually and collectively) in methods that use a dual diaphragm mechanical thermoforming process to form composite materials.
[0015] The applicant has found that the use of a single polymer, i.e., a single layer polymethylpentene (PMP) film, as a release film for high temperature double diaphragm molding (DDF) makes it possible to obtain composite parts of complex structure that can be used over a wide temperature range and therefore can be used as diaphragms in both the automotive and aerospace markets. Furthermore, the polymethylpentene film provides a visually excellent surface finish of the cured composite part after curing without signs of surface voids or weave distortion and without film breakage or while maintaining the integrity of the film.
[0016] In addition, the PMP film has the advantage of being easily self-peeled, thereby preventing transfer and / or contamination from the cured composite to the film and / or from the film to the composite.
[0017] The present invention therefore relates to the use of a monolayer polymethylpentene film as a release film in a method for molding a composite material, said method comprising the steps of: (a) disposing a substantially planar composite material between an upper polymethylpentene film and a lower polymethylpentene film by forming a pocket between the films to receive the composite material; (b) bringing the upper polymethylpentene film and the lower polymethylpentene film into intimate contact with the composite material, thereby forming a layered structure, and the composite material being held stationary between the upper polymethylpentene film and the lower polymethylpentene film until heat or force is applied to the layered structure; (c) optionally preheating the layered structure in a heating device at a temperature sufficient to reduce the viscosity of the composite material or soften the film; (d) placing the layered structure into a press tool including a male mold and a corresponding female mold separated by a gap, each of the male and female molds having independently non-planar molding surfaces; (e) compressing the layered structure between the male and female molds by closing the gap between the male and female molds; and (f) maintaining the male and female molds in a closed position until the viscosity of the layered structure reaches a level sufficient to maintain the molded shape; Includes.
[0018] According to the present invention, the polymethylpentene film is self-releasing, i.e., the film can be easily peeled off the final molded composite part and / or the molded assembly can be easily peeled off the tooling, which provides obvious advantages in protecting the tooling, such as reducing tool wear and eliminating the need to apply mold sealers or release agents between molds, reducing the cost of touch work and final parts, and thus facilitating the production of full-scale composite structures.
[0019] Typically, the polymethylpentene films used in the present invention contain at least about 99% by weight, particularly at least 99.25% by weight, of poly(4-methyl-1-pentene). The polymethylpentene films may also contain polymer additives such as heat stabilizers, processing stabilizers, antistatic agents, lubricants, and the like.
[0020] In accordance with the present invention, polymethylpentene films are used for high temperature double diaphragm forming (DDF) of complex composite structures using a press. The films are suitable for use over a wide cure temperature range, i.e., cure temperature T cure The present invention has the advantage that it can be used in the range of about 120 to about 200°C, and therefore can cover both the range of about 120 to about 170°C, particularly about 120 to about 150°C, which corresponds to the specifications of the automotive market, and the range of about 150 to about 190°C, particularly about 160 to about 190°C, which corresponds to the specifications of the aerospace and UAM markets.
[0021] Thus, the polymethylpentene film used as the release film in the present invention exhibits unique properties.
[0022] A given curing temperature T between about 120 and about 200°C cureIn this case, the film can ensure that there is no melting and / or breakage during the formation of the composite part, and can ensure sufficient peel performance. Thus, in some embodiments, the polymethylpentene film has a melting temperature of about 205° C. or more, preferably 210° C. or more.
[0023] In some embodiments, the thickness (t) of the polymethylpentene film depends on the shape of the composite part and ranges from about 10 microns to about 200 microns, particularly from about 20 microns to about 150 microns, such as from 25 microns to about 100 microns. Preferably, the film has a thickness of about 30 microns to about 80 microns. This thickness allows for desirable mechanical performance of the film and prevents wrinkling of the film during preheating and breakage during formation of the composite part.
[0024] In some embodiments, the polymethylpentene film has an elastic modulus (E) in the range of about 400 to about 900 MPa, preferably about 550 to about 850 MPa, and a tensile strength (σ) in the range of about 10 to about 50 MPa, preferably about 15 to about 30 MPa, which can help prevent film breakage when forming composite parts.
[0025] A specified T in the range of about 120 to about 200°C cure The films used in the present invention have a particular elongation at break (ε) to ensure that the film can achieve the desired part shape without breaking during forming at ambient temperature T. In some embodiments, the polymethylpentene film exhibits an elongation at break (ε) in either the machine or transverse direction in the range of about 50 to about 550%, preferably 110 to about 500%, and particularly about 150 to about 450%, at a speed of about 8 mm / sec at ambient conditions, where T ambient The temperature is typically about 20 to about 25°C.
[0026] Such films have a sufficiently large width so as not to limit the size of the composite part. In some embodiments, the product width of the polymethylpentene film is about 1.2 m or more. Preferably, the product width is about 1.5 m or more.
[0027] Thus, in a preferred embodiment, the polymethylpentene film used according to the present invention is A melting temperature (T melt ), A thickness (t) in the range of about 10 microns to about 200 microns, in particular about 20 microns to about 150 microns, in particular about 30 microns to about 80 microns; An elastic modulus (E) in the range of about 400 to about 900 MPa, preferably about 550 to about 850 MPa; a tensile strength (σ) in the range of about 10 to about 50 MPa, preferably about 15 to about 30 MPa, and an elongation at break (ε) in the range of about 50 to about 550%, preferably 110 to about 500%, particularly about 150 to about 450%, in either the machine or transverse direction at a speed of about 8 mm / s at ambient conditions; has.
[0028] The thermal properties of the films, including the melting temperature, can be determined using Differential Scanning Calorimetry (DSC) according to ASTM D3418, for example by using a differential scanning calorimeter such as a TA Instruments Q2000.
[0029] The mechanical properties of the film, such as tensile strength, tensile modulus, and elongation at break, can be determined using the thin film tensile strength and elongation test (ZM45) according to ASTM D882-09, for example by using a Zwick Z250 testing machine. Typically, polymethylpentene is a thermoplastic polyolefin that can be obtained by general-purpose equipment for polypropylene and polyethylene. For example, polymethylpentene can be processed using standard thermoplastic processing methods such as injection molding, compression molding, blow molding, rotational molding, extrusion, and wire coating. Furthermore, polymethylpentene films can be obtained by blow molding or extrusion lamination techniques. Such processes are known to those skilled in the art.
[0030] According to one embodiment of the present invention, the polymethylpentene film can be recycled and reused in the composite molding method claimed in the present invention. For example, after the used polymethylpentene film is peeled off from the final composite material, this film can be granulated and then extruded, typically using extruders known in the art, to obtain new films that can be used in the composite molding method, especially the above-mentioned method.
[0031] The term "substantially planar" as used herein refers to a material having one plane that is significantly larger (e.g., at least 2, 3, 4, or 5 times larger, or more) than the other two planes. In some embodiments, a substantially planar material has a variation in thickness along its largest plane. For example, a composite material may include pad-ups (i.e., a local increase in the amount of plies) or ply drops (i.e., a local decrease in the amount of plies), changes in material, and / or reinforcement materials, such as areas where the composite material transitions, for example, to a fabric. In another embodiment, a substantially planar material exhibits minimal variations in thickness along an area of the composite material. For example, the term substantially planar may mean that the composite material has an overall thickness variation of + / - 15% or less over 90% of the area. In some embodiments, the thickness variation is ±10% or less over 90% of the area. Substantially planar is not intended to refer to a completely flat material, and includes materials that have slight variations in concave and / or convex shapes.
[0032] In the context of the present invention, the method of forming a composite material can use either a framed assembly or a frameless assembly. In some embodiments, the method includes the use of a framed assembly. The upper and lower films are held together by a structural frame including a top frame, a middle frame, and a bottom frame, in which: The lower film is held between the bottom frame and the central frame, The upper film is held between a central frame and a top frame.
[0033] In a preferred embodiment, the method includes the use of a framed assembly.
[0034] In certain embodiments, the pocket that contains the composite material is defined by a structural frame that contains the composite material held between the films. In certain embodiments, the substantially planar composite material is placed between the top and bottom films. This forms a pocket that contains the composite material between the films. For example, a bottom film having a top surface and a bottom surface can be placed such that its bottom surface is in contact over the perimeter of the bottom frame. The composite material can then be laid on top of the bottom film, then the center frame can be placed on top of the bottom film, followed by the top film, and finally the top frame against the top film. This arrangement forms a pocket between the bottom and top films that contains the composite material layer. In some embodiments, the center frame may be omitted. Such top, center (if present), and bottom frames define a perimeter that maintains the shape of the polymethylpentene film, for example, by placing clamps or other fastening means at predetermined intervals around the perimeter. Such top, center, and bottom frames can be manufactured based on the size and shape of the composite material to be molded. Optionally, pre-fabricated structural support frames for use with conventional metal or composite press tools (eg, from manufacturers such as Langzauner or Schubert) are known in the art.
[0035] In some embodiments, the central frame may include a means for removing air, such as a vacuum port or other valve. The vacuum port, if present, is connected to a vacuum source (e.g., a vacuum pump). In some embodiments, the pocket that contains the composite material may be an enclosed pocket, such as an airtight enclosed pocket, whereby the structural frame is positioned all around the composite material to prevent air or contaminants from entering the pocket.
[0036] The upper and lower films are in intimate contact with the composite material to form a layered structure. This can be accomplished, for example, by applying a vacuum pressure between the upper and lower films. In another embodiment, this can be accomplished by physically applying pressure (e.g., by hand or mechanical means) to the upper and / or lower films to remove the air. Vacuum pressure may be desirable in certain cases, for example, to extract most of the residual air that may interfere with molding performance, thereby minimizing deformation or wrinkling of the composite material (or its components) or film. The vacuum also prevents wrinkling of the film and increases the stability of the entire assembly. The use of vacuum pressure can also help maintain fiber alignment, support the material during processing and molding, and / or help maintain a desired thickness at elevated temperatures. As used herein, the term "vacuum pressure" refers to a vacuum pressure of less than 1 atmosphere (or less than 1013 mbar). In some embodiments, the vacuum pressure between the films is set to less than about 1 atmosphere, less than about 800 mbar, less than about 700 mbar, or less than about 600 mbar. In some embodiments, the vacuum pressure between the films is set to about 670 mbar. At this point, whether by vacuum or other means, such as mechanical means, the composite material is held tightly between the films and is therefore immobile until heat or force is applied. Such an immobile layered structure may be advantageous, for example, because the composite material held within the layered structure is not only kept immobile in its position with sufficient tension across the X and Y axes, but is also indexed. That is, the composite material may be placed (e.g., by automated means) at a specific location between the films within the immobile layered structure. This indexed immobile layered structure may then be placed (e.g., by automated means) at a specific location on a press tool (described in more detail herein below) such that the press tool is consistently engaged with a predetermined area of the composite material.This allows the stationary layered structure to be reliably used to produce multiple copies of a molded product without the need to individually index each composite interstices.
[0037] In some embodiments, the composite material may be machined according to the pattern prior to step (a).
[0038] The layered structure may optionally be preheated in a heating device. The layered structure may be placed in the heating device manually or by automated means, such as by using an automated shuttle. The heating device may be any heater that can be used to form or mold metal or composite products, such as a contact heater or a non-contact heater (i.e., ceramic or infrared (IR) heater). In some cases, this preheating softens the upper and lower films, such that they are more flexible during the formation of the final molded product. In some cases, this preheating brings the composite material held in the layered structure to a desired viscosity or temperature, allowing complex shapes to be formed from a flat initial layup. Preheating can be done in a heating device heated to a temperature greater than about 75°C, 100°C, 125°C, 150°C, 175°C, 190°C. The temperature can be adjusted, for example, depending on the components in the composite material. Such preheating is advantageous, for example, when it is desired to minimize heating of the press tool and / or minimize the time the layered structure is in the press tool.
[0039] To form the final molded product, the layered structure is placed in a press tool. In some embodiments, no vacuum pressure is applied to any part of the press tool. In another embodiment, a vacuum is applied locally to the tool surface, for example to remove air trapped between the layered structure and the tool. However, in such embodiments, the vacuum is typically not used as a force to form the shape of the final molded product. The layered structure can be placed in the press tool manually or by automated means, for example using an automated shuttle. The press tool typically includes a male mold and a female mold, which are separated by a gap. Each mold has a non-planar molding surface. In some embodiments, a release agent can be added to the male mold, the female mold, or both. Such a release agent can be useful, for example, to remove the molded part from the mold while it is still at a temperature above ambient temperature. In some embodiments, a release agent is not required. The molding surface is fixed, i.e., it is not reconfigurable. The molding surfaces are also typically congruent, i.e., the male mold corresponds approximately to the inverse of the female mold, and in some embodiments can be perfectly congruent. However, in some embodiments, the male and female molds are adapted to have a varying thickness between them when closed, hi certain embodiments, the layered structure is disposed in the gap between the male and female molds at a certain predetermined distance.
[0040] The layered structure is then compressed between the male and female molds by closing the gap between them (step (e)). In some embodiments, this is achieved by partially closing the gap between the male and female molds to form a smaller gap between the molds. This smaller gap is then closed after a certain time or viscosity is reached. "Closing the gap" is understood to mean compressing the molds such that a predetermined final cavity thickness along the Z axis is obtained between the molds. The final cavity thickness can be adjusted, for example, by controlling where the molds stop relative to each other, the choice of thickness can be made by the mold operator, and it depends on the nature of the final molded product. In some embodiments, the final cavity thickness is substantially uniform. That is, the process produces a double-sided molded final product whose thickness varies by less than 5%. In some embodiments, the process produces a final molded product having a thickness that varies by less than about 4%, for example, less than about 3%, less than about 2%, or even less than about 1%. In another embodiment, the male and female tools may be configured to provide a cavity thickness that varies purposefully across the X and Y axes.
[0041] In certain embodiments, the male and female molds are maintained at a temperature higher than the ambient temperature. For example, they may be maintained at a temperature of about 75°C, 100°C, 125°C, 150°C, 175°C, 200°C, or even higher, particularly, for example, at a temperature of about 120°C to 200°C. This temperature can be adjusted depending on the identity (as well as viscosity and reactivity) of the components in the composite. The mold can be maintained at a temperature above the softening point of, for example, the binder or matrix material used in the composite. In some embodiments, the composite comprises a thermosetting material, and the mold is maintained at a temperature of about 100°C to 200°C. The binder or matrix material in the composite is in a solid phase at ambient temperatures (20°C to 25°C), but softens when heated. This softening allows the composite to be molded in a press tool, conforming the flat preform to the shape of the final part.
[0042] In some embodiments, particularly for cured composite parts for the automotive market, the mold is maintained at a temperature between about 120° C. and 160° C. In some other embodiments, particularly for cured composite parts for the UAM and aerospace markets, the mold is maintained at a temperature between about 150° C. and about 190° C.
[0043] In some embodiments, the male and female molds are maintained in a closed position for a predetermined time to form a molded structure. For example, in some embodiments, the mold is heated and maintained in a closed position until a desired viscosity or temperature is reached. In some embodiments, the viscosity of the composite material is about 1.0×10 8 The mold is maintained in the closed position until the viscosity of the composite material is less than 100 mPa. In some embodiments, the mold is heated and maintained in the closed position until crosslinking of the binder or matrix material begins. In other embodiments, the mold is not heated but is maintained in the closed position for a time sufficient for the material to maintain its molded shape. The mold can be maintained in the closed position for, for example, about 1 minute to about 60 minutes, for example, about 5 minutes to about 20 minutes, or for example, about 1 minute to about 10 minutes. The length of time the mold is maintained in the closed position depends on many factors, such as the identity of the composite material and the temperature of the mold.
[0044] In a particular embodiment, the male mold is moved through the layered structure while the female mold remains stationary. In another particular embodiment, the female mold is moved through the layered structure while the male mold remains stationary. In another embodiment, the female mold does not remain stationary but moves at a slower speed than the male mold (so that the male mold still functions primarily as the forming surface). In yet another embodiment, both molds move at approximately the same speed to close the gap between the molds. The molds are moved at a speed and final pressure sufficient to deform / mold the composite material into the desired shape. For example, the molds may be moved at a speed of about 0.4 mm / s to about 500 mm / s, particularly about 0.7 mm / s to about 400 mm / s, particularly about 1 mm / s to about 350 mm / s, such as about 5 mm / s to 350 mm / s or about 50 mm / s to 300 mm / s. Additionally, the mold may be moved to a final pressure of about 30 psi to about 1000 psi, particularly about 100 psi to about 800 psi, or about 250 psi to about 750 psi. In some embodiments, the mold is moved at a speed and final pressure selected to control the thickness of the final molded product while avoiding wrinkle formation and distortion of the structural fibers. Additionally, the mold may be moved to a speed and final pressure selected to allow for rapid formation of the final molded part.
[0045] The gap between the male and female molds is then opened. While the molded structure remains on the press tool, it is allowed to cool to below the glass transition temperature of the binder or matrix material. However, in some embodiments, the molded structure is removed from the press tool before it cools below the glass transition temperature of the binder or matrix material. Due to the use of the polymethylpentene release film of the present invention, the molded structure is more easily removed from the press tool. Once the binder or matrix material cools below its glass transition temperature, it returns to a solid phase and the composite retains its newly formed shape. If the composite is a preform, such a preform retains its desired shape for subsequent resin infusion.
[0046] After the molded structure is obtained, the clips and / or fasteners are released and the various frames are removed from the film, after which the film and cured composite part are removed and the film is peeled away from the cured composite part.
[0047] According to the present invention, the polymethylpentene film is self-releasing, thus allowing the film to be easily peeled off of the final molded part to provide a visually excellent surface finish on the molded composite part after curing without any signs of surface voids or weave distortion, while allowing the film to be recycled and reused in subsequent cycles of the dual diaphragm mechanical thermoforming process.
[0048] Additionally, if desired, the film may be temporarily retained on the final molded product, for example, a temporary film may be desired to protect the part from the environment, e.g., contamination, prior to further processing, i.e., finishing / painting, etc.
[0049] The term "composite material" as used herein refers to an assembly of structural fibers and binder or matrix materials. The structural fibers may be organic fibers, inorganic fibers, or mixtures thereof, including commercially available structural fibers such as carbon fibers, glass fibers, aramid fibers (e.g., Kevlar), high modulus polyethylene (PE) fibers, polyester fibers, poly p-phenylene-benzobisoxazole (PBO) fibers, quartz fibers, alumina fibers, zirconia fibers, silicon carbide fibers, other ceramic fibers, basalt, natural fibers, and mixtures thereof. However, end applications requiring high strength composite structures will typically use fibers with high tensile strength (e.g., ≧3500 MPa or ≧500 ksi). Such structural fibers may include one or more layers of fibrous materials in any conventional configuration, including, for example, unidirectional tape (unitape) webs, nonwoven mats or veils, woven fabrics, knitted fabrics, non-crimp fabrics, fiber tows, and combinations thereof. It should be noted that structural fibers may be included as one or more plies throughout all or part of the composite, or with localized thickness increases / decreases, in the form of pad-ups or ply drops.
[0050] The fibrous material is held in place and stabilized by the binder or matrix material, so that the alignment of the fibrous material is maintained and the stabilized material can be stored, transported, and handled (e.g., molded or otherwise transformed) without fraying, unraveling, tearing, buckling, wrinkling, or otherwise reducing the integrity of the fibrous material. Fibrous materials held by a small amount of binder (e.g., typically less than about 10% by weight) are typically referred to as fibrous preforms. Such preforms would be suitable for resin infusion applications such as RTM. The fibrous material may also be held by a large amount of matrix material (commonly referred to as "prepreg" when referring to fibers impregnated with a matrix) and thus would be suitable for forming a final product without further addition of resin. In certain embodiments, the binder or matrix material is present in the composite in an amount of at least about 30%, at least about 45%, at least about 40%, or at least about 45%.
[0051] The binder or matrix material is typically selected from thermoplastic polymers, thermosetting resins, and combinations thereof. When used to form preforms, such thermoplastic polymers and thermosetting resins can be introduced in a variety of forms, such as powders, sprays, liquids, pastes, films, fibers, and nonwoven veils. The means for utilizing these various forms are generally known in the art.
[0052] Thermoplastic materials include, for example, polyesters, polyamides, polyimides, polycarbonates, poly(methyl methacrylate), polyaromatics, polyesteramides, polyamideimides, polyetherimides, polyaramids, polyarylates, polyaryletherketones, polyetheretherketones, polyetherketoneketones, polyacrylates, poly(ester)carbonates, poly(methyl methacrylate / butyl acrylate), polysulfones, polyarylsulfones, copolymers thereof, and combinations thereof. In some embodiments, the thermoplastic material may also include one or more reactive end groups, such as amine or hydroxyl groups, that are reactive towards epoxides or curing agents.
[0053] Thermosetting materials include, for example, epoxy resins, bismaleimide resins, formaldehyde condensation resins (including formaldehyde-phenolic resins), cyanate resins, isocyanate resins, phenolic resins, and mixtures thereof. The epoxy resins may be mono- or polyglycidyl derivatives of one or more compounds selected from the group consisting of aromatic diamines, aromatic primary monoamines, aminophenols, polyhydric phenols, polyhydric alcohols, and polycarboxylic acids. The epoxy resins may be multifunctional (e.g., difunctional, trifunctional, and tetrafunctional epoxies).
[0054] In some embodiments, combinations of thermoplastic polymers and thermosets are used in composites. For example, certain combinations may act synergistically with respect to flow control and flexibility. In such combinations, the thermoplastic polymer provides flow control and flexibility to the blend and dominates the typically low viscosity, brittle thermoset.
[0055] The use of the particular polymethylpentene film described above not only aids in the shaping of the composite, for example by maintaining the composite in a fixed position with sufficient tension across its X and Y axes, but also provides important additional functional benefits. For example, this arrangement protects the composite blank from environmental contaminants such as impurities in the air or on the tooling machine. This protection allows the use of conventional press tools (which cannot otherwise be handled) to process the two-dimensional preform into three-dimensional complex shapes, allowing significantly more complex three-dimensional shapes than vacuum forming or reconfigurable tooling techniques. Furthermore, the use of the dual diaphragm arrangement allows the removal of the demolding process from the entire process.
[0056] Thus, the dual diaphragm mechanical thermoforming process described herein provides an effective and efficient means for producing complex three-dimensional composite structures from two-dimensional flat preforms in an automated manner, which can be employed over a wide temperature range to provide a visually excellent surface finish of the cured composite parts after curing without any signs of surface voids or weave distortion for both automotive, UAM, and aerospace markets. Three-dimensional composite structures can be produced on a large scale and in rapid repeatable cycles. For example, three-dimensional composite structures can be formed from substantially planar composite blanks in 1-10 minute cycles, or 5-20 minute cycles, or 10-30 minute cycles, or 20-60 minute cycles, depending on the desired part and composite material. Such rapid and repeatable processes are suitable for the production of automotive parts and panels such as hoods, trunks, door panels, fenders, and wheel wells, as well as aerospace / UAM parts such as frames, ribs, spars, and doors. EXAMPLES
[0057] The following examples are for illustrative purposes only and should not be construed as limiting the scope of the appended claims.
[0058] Example 1: Framed dual diaphragm mechanical thermoforming using high temperature PMP film and epoxy prepreg according to the present invention A lower flexible diaphragm made of 76 micron polymethylpentene (PMP) film was placed on the bed holding the bottom frame. This film exhibits the characteristics reported in Table 1.
[0059] [Table 1]
[0060] Carbon fiber reinforced epoxy composite blanks (Solvay, formerly Cytec Industries, CYCOM TM A 100 mm thick flexible diaphragm (EP2750) was placed on top of the lower flexible diaphragm, followed by a central frame with vacuum ports. An upper flexible diaphragm, made of the same film as the lower flexible diaphragm, was then placed over the central frame and the composite blank. The upper, central, and lower frames were clamped together, thereby forming a vacuum-tight seal and an enclosed pocket surrounded by the lower flexible diaphragm, the upper flexible diaphragm, and the central frame. A vacuum was then applied to remove air from between the upper and lower flexible diaphragms until a minimum vacuum pressure of 670 mbar was reached. At that point, the composite blank was firmly supported by both diaphragms, forming a motionless layered structure.
[0061] The layered structure was then shuttled into a ceramic non-contact heating device where it was heated to 150°C. After the temperature of the outer film reached a minimum of 130°C, it was shuttled into a press tool containing matching male and female dies configured in the shape of an automotive B-pillar structural part. The female die was then moved towards the male die at a rate of approximately 4mm / sec (250mm / min). The male die was kept stationary and both dies were held at 180°C until crosslinking began. The molded structure was removed from the press tool while still hot and allowed to cool after removal. The process of molding the composite blank was 25 minutes from start to finish (i.e., from initial placement of the lower flexible diaphragm to formation of the final shape).
[0062] No film breakage was observed in the longitudinal direction and negligible film breakage was observed in the transverse direction. Furthermore, no film wrinkling was observed. The release performance of the PMP film according to the present invention was very good, although some self-peeling was observed upon cooling. Furthermore, the surface finish of the composite part was improved, the surface finish was glossy, and no transfer was observed from the film to the composite part or from the composite part to the film.
[0063] The thermal properties of the films were determined using differential scanning calorimetry (DSC) by using a differential scanning calorimeter TAQ 2000. A heat / cool / heat procedure was applied and the temperature range from -30°C to 300°C was screened with cooling and heating rates of 10°C / min.
[0064] The mechanical properties of the films were determined according to ASTM D882-09 using a Zwick Z250 testing machine. The films were tested in both the machine and transverse directions at a test speed of about 8 mm / s (500 mm / min) at ambient conditions of 23° C. and 50% relative humidity.
[0065] Example 2: Comparative Example - Framed Dual Diaphragm Mechanical Thermoforming Using High Temperature Nylon Film and Epoxy Prepreg A lower flexible diaphragm made of 65 micron nylon (PA6,66) film (Aerovac / Solvay, formerly Cytec Industries, SV3000) was placed on the bed that holds the bottom frame.
[0066] Carbon fiber reinforced epoxy composite blanks (Solvay, formerly Cytec Industries, CYCOM TM A 100 mm thick flexible diaphragm (EP2750) was placed on top of the lower flexible diaphragm, followed by a central frame with vacuum ports. An upper flexible diaphragm, made of the same film as the lower flexible diaphragm, was then placed over the central frame and the composite blank. The upper, central, and lower frames were clamped together, thereby forming a vacuum-tight seal and an enclosed pocket surrounded by the lower flexible diaphragm, the upper flexible diaphragm, and the central frame. A vacuum was then applied to remove air from between the upper and lower flexible diaphragms until a minimum vacuum pressure of 670 mbar was reached. At that point, the composite blank was firmly supported by both diaphragms, forming a motionless layered structure.
[0067] The layered structure was then shuttled into a ceramic non-contact heating device where it was heated to 150°C. After the temperature of the outer film reached a minimum of 130°C, it was shuttled into a press tool containing matching male and female dies configured in the shape of an automotive B-pillar structural part. The female die was then moved towards the male die at a rate of approximately 4mm / sec. The male die was kept stationary and both dies were held at 180°C until crosslinking began. The molded structure was removed from the press tool while still hot and allowed to cool after removal. The process of molding the composite blank was 25 minutes from start to finish (i.e., from initial placement of the lower flexible diaphragm to formation of the final shape).
[0068] It can be observed that the film breakage, melting, and / or cracking was negligible in both the machine and cross direction orientations due to the good thermal and mechanical performance of the film. Nevertheless, some film wrinkling was observed on the part surface due to the high tensile strength of the film. However, after DDF treatment, the peel performance was very poor because the film showed strong chemical adhesion to the cured part surface. Therefore, it was not possible to quantify the quality of the part surface.
[0069] Example 3: Recycling of PMP film Poly(4-methyl-1-pentene) (PMP) films of 75 microns thickness were granulated through a 20 mm diameter Collin single screw extruder (L / D=25 / 1) equipped with three heating zones. The temperature profile of the extruder was set at 230, 250, and 260°C for zones 1-3. The melt temperature was 260°C. The extrudate was passed through a chill roll equipped with a roll at room temperature and then granulated using a Scheer granulator. The collected granules were then extruded through a 30 mm diameter Collin single screw extruder (L / D=25 / 1) equipped with three heating zones. The temperature profile of the extruder was set at 230, 250, and 260°C for zones 1-3. The melt temperature was 260°C. The extrudate was passed through a film die maintained at 260°C and then cast onto a roller maintained at 50°C followed by a chill roll set at room temperature. The resulting film thickness was 3 mils (75 μm).
[0070] The thermal properties of the films were determined using differential scanning calorimetry (DSC) by using a differential scanning calorimeter TAQ 2000. A heat / cool / heat procedure was applied and the temperature range from -30°C to 300°C was screened with a cooling and heating rate of 10°C / min.
[0071] The mechanical properties of the films were determined according to ASTM D882-09 using a Zwick Z250 testing machine. The films were tested in both the machine and transverse directions at a test speed of about 8 mm / s (500 mm / min) at ambient conditions of 23° C. and 50% relative humidity.
Claims
1. 1. Use of a monolayer polymethylpentene film as a release film in a method for molding a composite material, said method comprising: (a) disposing a substantially planar composite material between an upper polymethylpentene film and a lower polymethylpentene film by forming a pocket between the films to receive the composite material; (b) placing said upper polymethylpentene film and said lower polymethylpentene film in intimate contact with said composite material, thereby forming a layered structure, said composite material being held stationary between said upper polymethylpentene film and said lower polymethylpentene film until heat or force is applied to said layered structure; (c) optionally preheating the layered construction in a heating device at a temperature sufficient to reduce the viscosity of the composite material or soften the film; (d) placing the layered structure into a press tool including a male mold and a corresponding female mold separated by a gap, the male mold and the female mold each independently having a non-planar molding surface; (e) compressing the layered structure between the male and female molds by closing the gap between the male and female molds; and (f) maintaining the male and female molds in a closed position until the viscosity of the layered structure reaches a level sufficient to maintain a molded shape; Including, use.
2. The polymethylpentene film is A melting temperature (T melt ), a thickness (t) ranging from about 10 microns to about 200 microns, particularly from about 20 microns to about 150 microns, particularly from about 30 microns to about 80 microns; - an elastic modulus (E) ranging from about 400 to about 900 MPa, preferably from about 550 to about 850 MPa; a tensile strength (σ) in the range of about 10 to about 50 MPa, preferably about 15 to about 30 MPa, and - Elongation at break (ε) in the range of about 50 to about 550%, preferably 110 to about 500%, in particular about 150 to about 450%, in either the machine or transverse direction at a speed of about 8 mm / s at ambient conditions; 2. The use according to claim 1, having the formula:
3. 3. The use according to claim 1 or 2, wherein step (e) comprises partially closing the gap between the male and female moulds such that a smaller gap is formed between the moulds, which smaller gap is subsequently closed after a certain time or viscosity is reached.
4. 3. The use according to claim 1 or 2, wherein the male mould and the female mould are maintained at a temperature higher than ambient temperature.
5. 5. The use according to claim 4, wherein the male mould and the female mould are maintained at a temperature above 100°C.
6. The use according to claim 4, wherein the male mold and the female mold are maintained at a temperature of about 120°C to about 160°C.
7. 5. The use according to claim 4, wherein the male and female moulds are maintained at temperatures of about 150°C and about 190°C.
8. 3. The use according to claim 1 or 2, wherein the polymethylpentene film is a recycled film.
9. 3. The use according to claim 1 or 2, wherein step (e) comprises closing the gap between the male and female molds at a speed of about 0.7 mm / sec to about 400 mm / sec while maintaining the male and female molds at a temperature above the softening point of the composite material.
10. 3. The use according to claim 1 or 2, wherein step (b) comprises applying a vacuum pressure of at least about 670 mbar between the upper and lower films.
11. The use according to claim 1 or 2, wherein the male and female moulds are maintained in a closed position for about 1 minute to about 60 minutes.
12. The upper and lower films are held together by a structural frame including a top frame, a middle frame, and a bottom frame, wherein: the lower film is held between the bottom frame and the central frame; 3. The use according to claim 1 or 2, wherein the upper film is held between the central frame and the upper frame.
13. The use according to claim 12, wherein the central frame provides a vacuum source to the assembly.
14. The use of claim 1 or 2, wherein the upper film and the lower film are held together by a structural frame including a top frame and a bottom frame, and both the lower film and the upper film are held between the bottom frame and the top frame.
15. 3. Use according to claim 1 or 2, wherein the layered structure is placed into the press tool and optional heating device by automated means.
16. 3. The use according to claim 1 or 2, wherein the composite material comprises structural fibres of a material selected from aramid, high modulus polyethylene (PE), polyester, poly-p-phenylene-benzobisoxazole (PBO), carbon, glass, quartz, alumina, zirconia, silicon carbide, basalt, natural fibres and combinations thereof.
17. 3. The use according to claim 1 or 2, wherein the composite material comprises a binder or matrix material selected from thermoplastic polymers, thermosetting resins, and combinations thereof.